(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2024)
José Fernández Madrid (1789-1830), doctor, poet and president during the independence of Gran Colombia, was part of the literate groups of the Creole elites who were tasked with symbolically establishing the imagined communities of the new Latin American States. This article, therefore, analyzes the way in which the author constructs a vision of the nation in his verses and traces the political consequences of his literary work. As such, it takes as its object of study various poems gathered in his 1889 anthology and identifies how Fernández Madrid projects a Latin-American identity through the opposition between an Iberian-you and an American-us. Likewise, it points out the mechanisms with which it vindicates the role of the Creoles –transferring the identification criteria from race to ideology–, shows the different possible nationalities that come into conflict in his stanzas and examines the configuration of the formula: «nation is equal to its people». Finally, it considers the constitutions of 1821 and 1826, with the aim of illuminating the way in which these ideological efforts acquired a legal and operational character in the Hispanic nations. Although it is not possible to establish a direct cause and effect relationship between poetry and laws, it is demonstrated that both phenomena were part of a more comprehensive process, in which the new independent States built their own identity that justified their sovereignty.